Mechanisms of labour exploitation: the case of Pakistan. Issue 1 (17th March 2020) - Arslan, Muhammad
Abstract : Purpose: The issue of exploitative labour practices has been a persistent and recurring problem in the textile and garment industry. Despite increased media, policy and practitioners attention the evidence base remains unexplored. The International Labour Organization (ILO) has acknowledged the presence of labour exploitation in global supply chains because of private sectors' employment practices. The purpose of this study is to apprehend views of multilevel stakeholders to explore the nature and driving mechanisms of exploitation. Design/methodology/approach: Semi-structured interviews were conducted with 76 respondents from 25 factories from 3 cities of Pakistan i.e. Faisalabad, Lahore and Gujranwala. Convenient and snowball sampling techniques were used because of the complexity of research settings. Transcribed data was analysed with the help of NVivo. Findings: Drawing on qualitative evidence, the study reveals that workers experience a range of exploitation at the workplace, which is unlikely to fall within the scope of severe exploitation. The findings reveal that three types of exploitation exist in Pakistan's textile and garment industry such as financial, physiological and psychological. Power inequality is the foundation and a fundamental cause of the endurance of exploitation. The study found three mechanisms that facilitate the endurance of exploitation, i.e. distance, profit and oppression. Research limitations/implications: The study contributes to supply chain literature by exemplifying power inequality. It is crucial for the government to step up efforts to stipulate a minimum wage rate in the textile and garment industry to alleviate labour exploitation. The findings provide motivation for policy and decision-makers to implement incremental changes to global supply chains to protect the rights and welfare of workers, according to the standards of social accountability 8000, the ILO and other world trade stakeholders. Originality/value: This study argues that the international and local instruments do not specifically address the severe labour exploitation in Pakistan textile and garment industry. Therefore, the need arises to develop a specific instrument to address the problem. In the absence of such an instrument, there is a piecemeal approach by international and local bodies towards the regulation of labour exploitation.